Recent Advances in Near‐Infrared Absorption Nanomaterials as Photoacoustic Contrast Agents for Biomedical Imaging. Issue 1 (3rd November 2014) - Zhang, Juchen; Qiao, Zengying; Yang, Peipei; Pan, Jie; Wang, Lei; Wang, Hao
Abstract Photoacoustic imaging (PAI) is an emerging whole‐body imaging modality offering high spatial resolution, deep penetration and high contrast in vivo. Signals for PAI are generated from contrast agents, where the laser‐generated optical energy is transferred to acoustic emissions and detected by an ultrasound transducer. A great deal of research over the past ten years has shown that near‐infrared absorption nanomaterials such as organic dye‐based nanoparticals, polymer‐based nanoparticles, carbon‐based nanomaterials and metallic nanomaterials are promising photoacoustic (PA) contrast agents, which can increase the imaging resolution, contrast and depth of detection. Hence, it is an attractive research field to develop new PA contrast agents. Herein, we reviewed this rapidly growing field and described the applications of nanomaterial‐based PA contrast agents for biomedical imaging. Particular focus was given to organic near‐infrared absorbing dyes including cyanine, porphyrin and boron‐dipyrromethene derivatives.